Financial Liberalization, Money Demand, and Monetary Policy in Asian Countries - Corker, Robert (Occasional Papers; Occasional Paper ;, 1991)
This study examines the financial reforms undertaken by nine Asian countries in the 1980s (Indonesia, Korea, Malaysia, Myanmar, Nepal, the Philippines, Singapore, Sri Lanka, and Thailand) and their implications for money demand and monetary policy.